MicroRNA warfare: how chickens combat Klebsiella variicola with gga-miR-2954 - Yin, Lei; Shen, Xuehuai; Yin, Dongdong; Hou, Hongyan; Wang, Jieru; Zhao, Ruihong; Qi, Kezong; Dai, Yin; Pan, Xiaocheng (Frontiers in Cellular and Infection Microbiology, 2025)
Klebsiella variicola is a member of Klebsiella pneumoniae complex and an emerging zoonotic pathogen. As part of the lymphatic system, the spleen plays a pivotal role in destroying invading pathogens. Various microRNAs (miRNAs) are involved in host resistance to pathogens. However, specific miRNAs that act against K. variicola remain unknown. Therefore, RNA sequencing (RNA-Seq) of the miRNA profile of the chicken spleen was conducted to further clarify the host immune response to K. variicola infection. Challenge of 7-day-old chicks with K. variicola strain AHKV-S01 caused severe damage and enlargement of the spleen. In total, 22 differentially expressed (DE) miRNAs (fold change>2, q< 0.05) were identified. Functional annotation analysis of the target genes of DE miRNAs found that signaling pathways related to innate immunity, inflammation, and metabolism were significantly enriched. Notably, expression of gga-miR-2954 was significantly upregulated in the infection group as compared to the control group. In vitro, gga-miR-2954 directly repressed luciferase reporter gene activity by binding to the 3′ untranslated regions of STAB1. Overexpression of gga-miR-2954 in HD11 macrophages significantly inhibited expression of STAB1, which is involved in activation of several proinflammatory cytokines. K. variicola induced damage to the spleen by over activation of inflammatory and innate immune responses. The observed changes to the miRNA expression profile of the chicken spleen elucidate host immune responses to K. variicola infection, providing critical insights for developing novel therapeutic strategies to enhance chicken resistance against this pathogen.